(untitled) (Economics and region, 2020)
The theoretical approaches to the definition of the essence of concepts "controlling" and "financial control" are generalized and analyzed. As a result, it is discovered that scientists consider financial control as a subsystem controlling an enterprise or as an enterprise management system as a whole. It is proposed the self-determination of financial control of joint activities. It is substantiated that financial control is a system of effective management of financial and economic activity of a joint venture, which includes planning, accounting, control, analysis, management information provision for achievement of strategic and operational objectives of joint venture. The strategic focus of financial control is emphasized.